The Key to Success:Building Speaking Competence Through Problem Based Learning (PBL) for Real Communication - Stella Prancisca (Jurnal Visi Ilmu Pendidikan, 2015)
Speaking is a crucial part in English as a foreign language teaching and learning because the success of English mastery can be measured if the students can speak in the target language (Nunan: 2003). Unfortunately, although English has been taught for many years in Indonesia, only a few of Indonesian students have a good mastery in speaking. There are many challenges that the students face. These include low mastery of English (pronunciation, vocabulary, and grammar), high use of mother tongue in English class, limited opportunities to explore the students’ potentials in speaking, speaking activities were dominated by talkative students, and  students who are not enthusiastic or interested in joining the speaking activities. To improve this condition, Problem Based Learning (PBL) can be a good alternative in teaching speaking. PBL is a motivating way to learn because learners are involved in active learning and working with real problems and what they have to learn in their class seen as important and relevant to their own lives. Speaking is no longer a repetition of drills or memorization of dialogue but it uses as a real communication.   This study is aimed at finding out whether the implementation of PBL improves the students speaking competence. It will also describe the teaching and learning conditions in which PBL is implemented in the classroom. Keywords: teaching speaking, PBL, real communication.